Response to One Interval Does Not Fit All: A Comment on "Optimizing Post-Activation Performance Enhancement in Athletic Tasks: A Systematic Review with Meta-analysis for Prescription Variables and Research Methods"...Lima L, Fontanetti G. One interval does not fit all: A comment on “Optimizing post-activation performance enhancement in athletic tasks: a systematic review with meta-analysis for prescription variables and research methods”. Sport Med. 2025;55(12):3201-3202. - Xu, Kai; Blazevich, Anthony J.; Boullosa, Daniel; Ramirez-Campillo, Rodrigo; Yin, MingYue; Zhong, YuMing; Tian, YuHang; Finlay, Mitchell; Byrne, Paul J.; Cuenca-Fernández, Francisco; Wang, Ran (Sports Medicine, 2025)
The letter discusses insights from a commentary on a recent meta-analysis regarding post-activation performance enhancement (PAPE) research. It emphasizes the need for adapting recovery intervals between tests based on specific test characteristics, agreeing with the commentary's suggestion that shorter intervals may be sufficient for certain tests, while longer recovery times are necessary for maximal intensity tests. The authors also highlight the importance of individualized recovery periods, noting that subjective feedback from athletes may not reliably indicate optimal recovery status. They call for further research to explore the stability of individualized responses over time and the influence of physiological differences on recovery and performance.